2007
DOI: 10.1007/s00128-007-9328-y
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Variation in Polycyclic Aromatic Hydrocarbon Concentrations in Eggs of Diamondback Terrapins, Malaclemys terrapin, from the Patuxent River, Maryland

Abstract: Aquatic organisms encounter a number of contaminants in their environments. Here, we report polycyclic aromatic hydrocarbon (PAH) concentrations detected in diamondback terrapin eggs collected from the Patuxent River, Maryland, one year after an oil spill. Data suggested a geographic difference in egg hydrocarbon concentrations. However, at one year after the oil spill, most PAH concentrations detected were low, were not correlated with the extent of shoreline oiling, and thus likely represent current backgrou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…The middle Patuxent River supports some commercial fishing and agriculture, but unlike some of the other, more polluted tributaries, it is not listed as a region of concern by the Chesapeake Bay Program [21; http://www.chesapeakebay.net/pubs/792.pdf] and concentrations of most sediment contaminants, including PCBs, are well below the effects range low as defined by the National Oceanic and Atmospheric Administration's National Status and Trends Program [22; ccma.nos.noaa.gov/publications/NCCOSTM47.pdf]. Terrapin eggs previously collected from this area showed low concentrations of polycyclic aromatic hydrocarbons following an oil pipeline rupture in 2000 but were not screened for any other contaminants at that time [23].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The middle Patuxent River supports some commercial fishing and agriculture, but unlike some of the other, more polluted tributaries, it is not listed as a region of concern by the Chesapeake Bay Program [21; http://www.chesapeakebay.net/pubs/792.pdf] and concentrations of most sediment contaminants, including PCBs, are well below the effects range low as defined by the National Oceanic and Atmospheric Administration's National Status and Trends Program [22; ccma.nos.noaa.gov/publications/NCCOSTM47.pdf]. Terrapin eggs previously collected from this area showed low concentrations of polycyclic aromatic hydrocarbons following an oil pipeline rupture in 2000 but were not screened for any other contaminants at that time [23].…”
Section: Methodsmentioning
confidence: 99%
“…pdf]. Terrapin eggs previously collected from this area showed low concentrations of polycyclic aromatic hydrocarbons following an oil pipeline rupture in 2000 but were not screened for any other contaminants at that time [23].…”
Section: Methodsmentioning
confidence: 99%
“…Hall et al (1983) reported concentrations of petroleum hydrocarbons in tissues of sea turtles exposed to oil after the Ixtoc spill in the Bay of Campeche, Mexico, in 1979. In freshwater turtles, studies have focused on PAH concentrations in eggs and subcutaneous fat (Bell et al 2006, Holliday et al 2008, Rowe et al 2009) or blood (Drabeck et al 2014, Meyer et al 2016) of turtles from known contaminated habitats. In general, information is lacking on baseline exposure, uptake and tissue distribution of parent and alkylated PAH homologs for juvenile and adult turtles.…”
Section: Contribution To the Theme Section 'Effects Of The Deepwater mentioning
confidence: 99%
“…Turtle eggs have been used to evaluate contamination of heavy metals (Tryfonas et al 2006), PAHs (Holliday et al 2008), PCBs (Dabrowska et al 2006;Kelly et al 2008), organochlorine pesticides and dioxins/furans (de Solla and Fernie 2004;Henny et al 2003). Estimating concentrations of contaminants using eggs has been suggested as a potential non-lethal way to monitor metal exposure for endangered marine turtles (Sakai et al 1995).…”
Section: Introductionmentioning
confidence: 98%